2009
DOI: 10.1242/jcs.042325
|View full text |Cite
|
Sign up to set email alerts
|

EFA6A encodes two isoforms with distinct biological activities in neuronal cells

Abstract: The processes of neurite extension and remodeling require a close coordination between the cytoskeleton and the cell membranes. The small GTPase ARF6 (ADP-ribosylation factor 6) has a central role in regulating membrane traffic and actin dynamics, and its activity has been demonstrated to be involved in neurite elaboration. EFA6A has been shown to act as a guanine nucleotide exchange factor (GEF) for ARF6. Here, we report that two distinct isoforms of the EFA6A gene are expressed in murine neural tissue: a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…It was recently shown that EFA6A promotes neurite extension, whereas EFA6s induces dendritic branching in cultured cortical neurons (Sironi et al . ). In mature neurons, the EFA6A‐Arf6 pathway regulates the development and maintenance of dendritic spines through the internalization of telencephalin and the downstream activation of the Rac1 pathway (Choi et al .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…It was recently shown that EFA6A promotes neurite extension, whereas EFA6s induces dendritic branching in cultured cortical neurons (Sironi et al . ). In mature neurons, the EFA6A‐Arf6 pathway regulates the development and maintenance of dendritic spines through the internalization of telencephalin and the downstream activation of the Rac1 pathway (Choi et al .…”
mentioning
confidence: 97%
“…EFA6A is a prototypical member of this family that coordinates endocytic trafficking with actin cytoskeleton reorganization (Franco et al 1999). The murine EFA6A gene gives rise to two splice variants, a 1025-aminoacid polypeptide (EFA6A) with a long N-terminal region containing a Sec-7 domain required for GEF activity toward Arf6 and a 393-amino-acid polypeptide (EFA6As) sharing a C-terminal 327-amino-acid region but lacking a Sec-7 domain, by the use of an alternative promoter (Sironi et al 2009). In the mouse brain, EFA6A, EFA6C, and EFA6D exhibit isoform-specific spatiotemporal expression.…”
mentioning
confidence: 99%
“…In particular, manual inspection revealed that this list contains some of the best known examples of transcripts localized to dendrites and/or associated with dendritic functions. Indeed, besides to a Camk2a probe not included in the training set, the list contained probes from Dendrin (Dnd) [35], [36], Psd (also known as Efa6a) [37], microtubule-associated protein 2 (Map2) [9], Git1 [38] and Spinophilin (Ppp1r9b) [39], [40]. Accordingly, visual inspection of the corresponding ABA images confirmed a significant signal enrichment in neuropil for many of the probes included in the list Table 2, as it is the case for the Rnf10 gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pcdh20, Cldn22, and Rnd1 may participate in cell adhesion, and the genetic variations in this process can cause synaptic dysfunction in PD (Chapman, ). The dysregulations of Psd, Cntnap1, and Capn11 can induce cytoskeletal abnormalities (Garcia‐Fresco et al ., ; Jetten et al ., ; Sironi et al ., ), which is linked to the pathogenesis of PD (Mila et al ., ). Nmbr can regulate the functions of 5‐hydroxytryptamine system (Yamano et al ., ), which may be involved in the development of PD through its interaction with the basal ganglia (Miguelez et al ., ).…”
Section: Discussionmentioning
confidence: 97%